Processing of performance errors predicts memory formation: Enhanced feedback‐related negativities for corrected versus repeated errors in an associative learning paradigm. (3rd October 2019) - de Bruijn, Ellen R. A.; Mars, Rogier B.; Hester, Rob
Abstract: Learning from errors or negative feedback is crucial for adaptive behavior. FMRI studies have demonstrated enhanced anterior cingulate cortex activity for errors that were later corrected versus repeated errors even when a substantial delay between the error and the opportunity to correct was introduced. We aimed at identifying the electrophysiological correlates of these processes by investigating the feedback‐related negativity (FRN) and stimulus‐locked P3. Participants had to learn and recall the location of 2‐digit targets over consecutive rounds. Feedback was provided in two steps, first a color change indicated a correct or incorrect response (feedback phase) followed by presentation of the correct digit information (re‐encoding phase). Behaviorally, participants improved performance from the first to the third round. FRN amplitudes time‐locked to feedback were enhanced for corrected compared to repeated errors. The P3 in response to re‐encoding did not differ between the two error types. The finding that FRN amplitudes positively predicted memory performance is consistent with the idea that the FRN reflects prediction errors and the need for enhanced cognitive control. Interestingly, this happens early during feedback processing and not at a later time point when re‐encoding of correct information takes place. The prediction error signal reflected in the FRN is usually elicited by performance errors, but may thus also play a role in preparing/optimizing the system for memory formation. This supports the existence of a close link between action control and memory processes even when there is a substantial delay between error feedback and the opportunity to correct the error. Abstract : Using EEG and a visual associative learning paradigm, we disentangled processing of initial negative feedback and later re‐encoding of correct information. The results showed that the amplitude of the feedback‐related negativity (FRN), but not the P3, positively predicted memory performance. This was specific for feedback processing and not at the later time point of re‐encoding. These findings support the idea that the FRN reflects prediction errors and the need for enhanced cognitive control.